Análise do desflorestamento nos municípios do estado do Pará entre os anos de 2000 a 2009 e a importância das áreas protegidas na contenção do desflorestamento - MONTEIRO, Elivelton Ferreira (Universidade Federal do Pará, 2015)
This work aims to demonstrate the process of deforestation in the municipalities of Pará state and the importance of protected areas and indigenous territories in curbing the same. The study area constitutes the state of Para, which has an area of 1,247,690 km², and its 143 municipalities. Data were collected at INPE Monitoring Project in the Brazilian Amazon Forest by Satellite - PRODES. The processing and analysis of vector data was performed using ArcView 3.3 software. Deforestation accumulated by the year 2009, the state of Pará is about 19.6%. Since the remaining forest cover is about 65%. Deforestation in Pará presents itself differently among the twelve regions of integration, deforestation is concentrated mainly in northeastern and southeastern regions of the state, and also along major highways. The proportion of deforestation is varied between the municipalities of Pará Of the 143 municipalities, 31 are between 0 and 15.5% of their lands deforested, represents 21.7% of the total, 16 municipalities (11, 2%) are entre15, 5% and 35.5%, 32 municipalities (22.4%) are between 35.5% and 55.5%, 24 municipalities (11.9%) are between 55.5 and 75, 5% and 40 municipalities are between 75.5% and 95.5% of deforestation their territories, representing 28%. Of the 143 municipalities, 24 are between 0 and 15.5% of their lands deforested, represents 16.8% of the total, 22 municipalities (15.4%) are entre15, 5% and 35.5%, 27 municipalities (18.9%) are between 35.5% and 55.5%, 27 municipalities (18.9%) are between 55.5 and 75.5%, and 43 counties are between 75.5% and 95.5 % of deforested their territories, which represents 30.1%. In the state of Pará today there are 117 protected areas, being a Military Area, occupying 1.7%, 71 Conservation Units (14 Full Protection and Sustainable Use of 57) and 45 indigenous lands, occupying 29.03% and 22 9%, respectively, totaling 53.6% of the total state. The proportion of protected areas varies greatly among municipalities in the state of Pará Of the 143 cities, 16 shows from 55.5% to 93.6% of their territory within protected areas, representing 11.2% of the total, 12 municipalities (8.4%) had between 35.5% to 55.5%, 23 municipalities (16.1%) had between 15.5% - 35.5%, 15 municipalities (10.5%) are between 5, 5% - 16.5%, and the vast majority, 77 municipalities are between 0 and 5.5% of their territory within protected areas, representing 53.8%. There was a significant and negative correlation between the proportion of deforestation and the proportion of protected areas in Pará (r =-0.66). The municipalities that have the highest percentage of protected areas are therefore those with the lowest proportion of deforested their territories. The analysis of deforestation in the inner and outer municipalities of Pará showed the large proportion of vegetation within these areas compared to its exterior.